ANALISIS PERSEPSI DAN REAKSI GABUNGAN KELOMPOK TANI (GAPOKTAN) TERHADAP PEMANFAATAN SIARAN TELEVISI SEBAGAI SUMBER INFORMASI PERTANIAN DI DESA SIDOMULYO, KECAMATAN ANGGANA, KABUPATEN KUTAI KARTANEGARA - Dina Lesmana (Universitas 17 Agustus 1945 Samarinda, 2013)
This study aims to analize perceptions and reactions of farmer’s group to used television as a source of agricultural information, and correlation of perception and reaction of gapoktan.The study was conducted in Sidomulyo Village, Subdistrict of Anggana, Kutai Kartanegara Regency in since September until November 2012.Sampling using stratified random method. From 420 farmers joined in Gapoktan,40 respondents drawn from different Farmer Groups (Poktan). Data taken in the form of primary data and secondary data.perception and reaction analysis with measurement scales of Likert. Correlation of perceptions and reactions were analyzed by chi-square, coefficient contingency, and coeffecient of Cramer’s V. Results of this study showedpoktanin the SidomulyoVillage, Subdistrict of Anggana, Kutai Kartanegara Regency have a positive perception by 60%, 32.5% neutral, and negative 7.5%. Reaction use television as a source of agricultural informationby 80% and20% not using. These results indicated that Gapoktan in SidomulyoVillage, Subdistrict of Anggana, Kutai Kartanegara Regency has a positive perception and using television as a source of agricultural information. The results also show perceptions and reactions have a significant correlation and very close.